Study of operating modes of STRAUS-R accelerator - Gordeev, V.S.; Myskov, G.A.; Nikolsky, V.S.; Sulin, N.N.; Akatov, G.N.; Utyumov, N.N.; Volkov, M.V.; Gusakov, P.V.; Drachyov, A.N.; Kudryavtsev, Yu.G.; Kopkin, A.Yu.; Potapin, V.I. (Вопросы атомной науки и техники, 2006)
The description of a pulsed electron accelerator STRAUS-R (3.5 MeV, 60 kA, 60 ns) and results of its experimental
research for two operation modes are given. In the mode of electron beam focusing the accelerator provides the focal spot of 3-4 mm diameter on a target and maximum exposure dose of 27 R at 1-m distance from the output window. In the irradiating mode the maximum dose achieves 36 R at 1-m distance from the target with inhomogeneity ≤ 30% within the area 0.36 m² (irradiation spot diameter is 0.6 m). Приведены описание и результаты исследований импульсного электронного ускорителя СТРАУС-Р (3,5 МэВ, 60 кА, 60 нс) в двух режимах его работы. В режиме фокусировки электронного пучка ускоритель обеспечивает получение на мишени фокусного пятна диаметром 3…4 мм при максимальной дозе тормозного излучения 27 Р на расстоянии 1 м от выходного фланца. В облучательном режиме максимальная доза тормозного излучения на расстоянии 1 м от мишени по оси ускорителя достигает 36 Р с неоднородностью ≤ 30% на площади 0,36 м² (диаметр пятна облучения 0,6 м). Наведено опис і результати досліджень імпульсного електронного прискорювача СТРАУС-Р (3,5 МеВ, 60 кА, 60 нс) у двох режимах його роботи. У режимі фокусування електронного пучка прискорювач забезпечує одержання на мішені фокусної плями діаметром 3...4 мм при максимальній дозі гальмівного випромінювання 27 Р на відстані 1 м від вихідного фланця. При опроміненні максимальна доза гальмового випромінювання на відстані 1 м від мішені по осі прискорювача досягає 36 Р с неоднорідністю ≤ 30% на площі 0,36 м² (діаметр плями опромінення 0,6 м).